Novel fluorescence probe for estimation of cysteine/histidine in human blood plasma and recognition of endogenous cysteine in live Hct116 cells - Reddy, Upendar G.; Agarwalla, Hridesh; Taye, Nandaraj; Ghorai, Suvankar; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new Cu(II)-complex is used as a ``Turn-On'' luminescence probe for specific detection of endogenous Cys in live Hct116 cells and Cys present in human blood plasma without any interference from other amino acids, especially GSH and Hcy. Difference in the mechanistic pathway for Cys and His recognition is discussed.

New imaging reagents for lipid dense regions in live cells and the nucleus in fixed MCF-7 cells - Ramu, Vadde; Ali, Firoj; Taye, Nandaraj; Garai, Bikash; Alam, Aftab; Chattopadhyay, Samit; Das, Amitava (Journal of Materials Chemistry B, 2015)
Two new uracil (U) and 5-flurouracil (5-FU) labeled ruthenium(II)-polypyridyl based cellular imaging reagents are reported. Confocal laser scanning microscopic images with live and paraformaldehyde (PFA) fixed MCF-7 cells are examined using these two low-cytotoxic reagents. Experimental results show that these two complexes, appropriately functionalized with U (1) and 5-FU (2), have specific affinity for the lipid dense regions like the endoplasmic reticulum, cell membrane, and cytoplasmic vacuoles in live MCF-7 cells, and dye internalization in these regions happened following an endocytosis pathway. Interestingly, these two complexes are found to be localized in the nucleus of the PFA fixed cells. For fixed cells, presumably the lipid layer disruption helped in the explicit localization of the complexes 1 and 2 in the cell nucleus through specific interaction with cellular DNA. Poor and non-specific internalization of an analogous model complex 3, without having a U or 5-FU moiety, reveals the definite influence of U or 5-FU as well as the role of lipophilicity of the respective complex 1 and 2 in the cellular internalization process. Apart from these, a large Stokes shift (similar to 160 nm) and an appreciably long lived (MLCT)-M-3 excited state (similar to 320 ns) in aq. buffer medium (pH 7.4) are other key features for complexes 1 and 2. Unlike the common nuclear DNA staining reagents like DAPI, these low-cytotoxic reagents are found to be highly stable towards photo-bleaching upon irradiation with 455 nm at the MLCT band for these complexes.

New turn on Pd2+-specific fluorescence probe and its use as an imaging reagent for cellular uptake in Hct116 cells - Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new coumarin-rhodamine conjugate is used as a specific probe for Pd2+ ions and this could even delineate Pd(II) from Pd(0) or Pd(IV) in aqueous buffer medium (pH similar to 7). Laser confocal microscopic studies reveal that efficient cellular internalization of this reagent helps in imaging the cellular uptake of Pd2+ as low as 0.1 ppm in Hct 116 cells. This reagent could even be used for estimation of Pd2+ in human urine samples.